IMPLEMENTASI HAK CUTI HAID TERHADAP PEKERJA/BURUH PEREMPUAN BERDASARKAN HUKUM KETENAGAKERJAAN - Rowifebiona Ratnawijaya; Benni Rusli; Kartika Dewi Irianto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The right to menstrual leave is regulated in Article 81 paragraphs (1) and (2) of Law Number 13 of 2003 concerning Manpower. This law is a legal umbrella that protects women's human and constitutional rights, which states that female workers / workers when menstruating feel pain and then notify employers, so they are not obliged to work on the first and second days of menstruation. And related to the technical implementation of taking leave is regulated in the employment agreement, company regulations, or collective labor agreement. But in its implementation, the realization of menstrual leave is very difficult to find. This study aims to find out how the implementation of menstrual leave for female workers / workers based on labor law in Payakumbuh City and what are the obstacles and solutions in its implementation. Based on the results of the study, studies on several state-owned and state-owned companies in Payakumbuh City found that none of them applied menstrual leave for various reasons. However, based on the study of the 'Data Collection Sheet' document from the Payakumbuh City Manpower and Industry Office, the author found that there are several private companies that apply menstrual leave. It is hoped that with this research, state/regional-owned companies in Payakumbuh City can improve their company regulations so that there are no contradictions with the Manpower Law. Because menstrual leave is leave that must be given and notified by the company to its workers.